Monomelic amyotrophy: Case report - (:unkn) unknown (My University, 2008)
Monomelic amyotrophy (MMA) is a benign motor neuron disorder. MMA is usually restricted to the upper limb, lower limb involvement is rare. MMA should be considered in differential diagnosis in patients presenting with amyotrophy involving lower and upper extremity behind other diagnosis. A rehabilitative approach can be useful for these patients to compensate for the atrophy and decreased muscle strength. In this report, we discussed the clinical and electrophysiological features of two cases with MMA and the literature is reviewed.
Keywords: Lower extremity; Monomelic amyotrophy; Motor neuropathy; Upper extremity